Nodulation, Growth, and Yield of Soybean (Glycine max L. Merrill) as Affected by Bio-, Organic, and Inorganic NPSB Fertilizers, and Lime in Assosa Zone, Western Ethiopia - Abiyot Abeje; Getachew Alemayehu; Tesfaye Feyisa (International Journal of Agronomy)
The productivity of soybean in Assosa Zone particularly in Assosa and Bambassi districts is very low due to poor soil fertility management practices that resulted in severe soil acidity and low N-fixing inoculants in the soil. Hence, this experiment was conducted during the main cropping season of 2019 and 2020 in Assosa and Bambassi districts to evaluate the effect of biofertilizers, organic fertilizers, inorganic NPSB fertilizers, and lime on nodulation, growth, and yield of soybean (Glycine max L. Merrill). Factorial combinations of two biofertilizer inoculants (without biofertilizer (B1) and SB12 plus MAR1495 biofertilizers at their recommended rates of 500 g·ha−1 (B2); two organic fertilizers: without fresh cattle manure (M1) and fresh cattle manure at 10 t·ha−1 (M2); two lime rates: without lime (L1) and lime at 5 t·ha−1 (L2); two inorganic NPSB fertilizers: NPSB at 9.5-23-3.5-0.05 (F1) and NPSB at 19-46-7-0.1 (F2) at their recommended rates for soybean) were laid out in a randomized complete block design with three replications. Effective nodules, leaf area index, and grain yield were collected and analyzed using SAS 9.1.3 software. Results of the experiment showed that effective nodules, leaf area index, grain yield, bulk density, pH, total nitrogen, available phosphorus, organic carbon, and cation exchange capacity were highly (P<0.01) affected by the interaction of bio-, organic, and inorganic fertilizers and lime at both locations and years. Across all treatments, the grain yield of soybean was increased in the second year, while it was lowest in the first year at both locations. Finally, the interaction of SB12 + MAR1495, 10 t·ha−1 fresh cattle manure, without lime, and NPSB at 19-46-7-0.1 increased the grain yield of soybean in both Assosa and Bambassi districts and should be adopted appropriately to enhance the productivity of soybean in the areas and similar agroecologies, while the interaction effect of SB12 + MAR1495, 10 t ha−1 FCM, 5 t·ha−1 lime, and NPSB at 19-46-7-0.1 improved soil physicochemical properties in both the districts and similar agroecologies.